THE DEVELOPMENT OF FINANCIAL ACCESS (Study Case in South Sulawesi) - Andrini, Retno .; Pandelaki, Glenn Nathaniel (FEB Universitas Sam Ratulangi Manado, 2017)
The importance of access to finance allows Bank Indonesia to improve financial access for the purpose such as increasing community access and public knowledge to financial services; Providing financial services and products according to the needs of society; Encouraging increased household wealth; Encouraging the growth of the local economy to support the sustainability of national economic growth; and Assist the reduction of the poor. This paper analyze how deep the development of financial access in South Sulawesi. It traces the financial development through the 2010s to the present. Finally, the paper makes an attempt to offer an explanation of development of financial access in South Sulawesi. Keywords : Financial access, South Sulawesi